Analisis Kinerja dari Faktor Kepemimpinan Kepala Sekolah, Reward, dan Motivasi (Studi Kasus Guru Pada SDIT Baitun Nanda Kecamatan Mutiara Pidie) - Nurrahmah, Nurrahmah; Yusuf, M.; Ilyas, Mohd. (peusangan, 2024)
The study analyzed the Principal’s Leadership Factors, Rewards, and Motivation to maintain performance, with a case study of 43 teachers at SDIT Baitun Nanda, Mutiara Pidie District. The method used was associative with a quantitative approach with path analysis. The results of the study showed that 1) teacher performance was influenced by the principal’s leadership factor, Rewards and teacher motivation, respectively by 48.37 percent, 59.88 percent and 40.49 percent. 2) Simultaneously, the principal’s leadership, rewards and motivation contributed to increasing teacher performance by 63,2 percent. 3) There is a causal relationship between the variables of leadership, rewards and teacher work motivation with a strong category.